Kemampuan Menulis Paragraf Aksara Jawa Menggunakan Metode Cycle Learning Kelas XI SMKN 1 Sayung Demak Tahun Ajaran 2022 - Mahakarti, Dewi Chandra; Sulanjari, Bambang; Werdiningsih, Yuli Kurniati (Universitas PGRI Semarang, 2023)
This study was motivated by the lack of ability of students of class XI RPL SMKN 1 Sayung in writing Javanese characters in Javanese subjects. Related to the formulation of the problem, the research examines a problem, namely how is the ability of students to write a paragraph using Javanese characters in class XI RPL SMKN 1 Sayung? This study aims to describe the results of the ability to write a paragraph using Javanese characters in class XI RPL SMK Negeri 1 Sayung 2022. This research is included in descriptive quantitative research by making One Shot Case Study as a design. This study uses a population of students in class XI RPL SMK Negeri 1 Sayung. Taking the sample by doing purposive sampling technique, in the study the sample was all students in class XI RPL SMK Negeri 1 Sayung which totaled 24 students. This data collection uses experimental techniques. It has become the basis of the analysis that has been studied, it is known that there are 24 students with the results of 20 students who have completed, namely 83% and there are 4 students who are not complete, namely as much as 17%. The resulting value of the class average on the test is 74 and already includes a value higher than the KKM determined by the school which is 65. The results obtained may indicate that writing paragraphs in Javanese language lessons is a difficult task for students of class XI RPL SMK Negeri 1 Sayung Demak. The data is obtained from the test of writing a Javanese paragraph using aspects of knowledge and skills. Students can know and understand how to write paragraphs in Javanese appropriately.